Melukai Diri sebagai Bahasa Emosi:Self-harm, Sistem Keyakinan Irasional, dan Spiritualitas Pada Mahasiswa Muslim di Tulungagung - Wikan Galuh Widyarto; Muslihati; IM Hambali; Adi Atmoko (Institut Agama Islam Negeri Curup, 2026)
Self-harm is a maladaptive emotion-regulation strategy experienced by university students facing intense psychological distress. This study aimed to explore the subjective experiences of Muslim university students who engaged in self-harm and to examine the roles of irrational belief systems and spirituality in their recovery process. Using a qualitative approach with an interpretative phenomenological design, data were collected from six Muslim undergraduate students in Tulungagung, Indonesia, consisting of five females and one male aged 20–22 years, who were in their fourth and eighth semesters. Data we re obtained through semi-structured interviews, observations, and documentation/life history, and were analyzed thematically using REBT-based coding. The findings generated three main themes: (1) self-harm as an emotion-regulation mechanism in the absence of a safe relational space, reinforced by frustration intolerance; (2) interpersonal trauma as the root of awfulizing and self-downing beliefs; and (3) recovery through belief-system reconstruction supported by relational support, meaningful activities, and Islamic spirituality. These findings indicate that self-harm should not be understood merely as deviant behavior, but as an expression of unresolved emotional distress maintained by irrational beliefs. The study highlights the need for culturally sensitive, trauma-informed, and spiritually integrated RREBT-based counseling interventions for Muslim university students experiencing self-harm tendencies.